2012
DOI: 10.1080/09291016.2011.605639
|View full text |Cite
|
Sign up to set email alerts
|

Chronokinetic study of cefalexin in postprandial and fasting volunteers

Abstract: Few researches were conducted on the circadian variation of b-lactam antibiotics in humans. The aim of the present study was to determine whether circadian variation of cefalexin pharmacokinetics exists in postprandial or fasting male volunteers. Cefalexin was given orally to subjects under postprandial conditions or after an 8-h fast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…One study narrated a 1.9-fold decrease in C max of cephalexin and cefroxadin in the fed state as compared to the fasting state after the administration of a similar dose of 250 mg [ 25 ]. In addition, AUC 0-inf was found to be slightly decreased in the postprandial state in two clinical studies, one of which was conducted in adults on cephalexin [ 24 ] and the other in infants and pediatrics comparing the PK of cephalexin, cephradine, cefaclor, and cefadroxil, whose values can be discerned in Table 5 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study narrated a 1.9-fold decrease in C max of cephalexin and cefroxadin in the fed state as compared to the fasting state after the administration of a similar dose of 250 mg [ 25 ]. In addition, AUC 0-inf was found to be slightly decreased in the postprandial state in two clinical studies, one of which was conducted in adults on cephalexin [ 24 ] and the other in infants and pediatrics comparing the PK of cephalexin, cephradine, cefaclor, and cefadroxil, whose values can be discerned in Table 5 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both cephalosporins (cephalexin and cefroxadin) showed a significant decrease in C max in the fed state, depicting delayed absorption in the gastrointestinal tract [ 25 ]. One study reported a greater C max of cephalexin at the 20th hour than at the 8th hour after the intake of food, which may show the effect of time in the postprandial state as compared to the fasting condition [ 24 ]. In another study, the effect of food on cephalexin and cephradine was promptly indicated by a decrease in C max and AUC 0-inf in comparison to cefadroxil and cefaclor, which may be due to changes in PK features of the latter that were considered to be the predecessors of the former [ 35 ].…”
Section: Discussionmentioning
confidence: 99%